Implementasi Total Quality Management (TQM) di SMP Negeri 1 Dlanggu Kabupaten Mojokerto - Nawawi, Syu'aib (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
TQM should be applied to every Islamic education unit in order to encourage the quality of excellent service to stakeholders. Because, in today's sharp world of global competition, many people talk about "quality" especially related to jobs that produce products or services.  A result is made because there are those who need it, and those needs develop along with the quality demands of the users. Recognizing this task, SMPN 1 Dlanggu, which has achieved many achievements in various fields both academically and non-academically, continues to improve services for students by completing various learning facilities, qualified human resources (teachers and employees), and coordinating/collaborating with related institutions. In its implementation, TQM has an influence. Among them, student achievement is increasing. Not only in academics, but also non-academics, the enthusiasm of the community to send their children to SMPN 1 Dlanggu is increasing. There is a good relationship / cooperation between all residents of Dlanggu Middle School 1, both internally and externally to jointly improve school quality